The non-coding RNA revolution in the cancer society - Calin, George (Henry Stewart Talks, 2015)
Cancer: a complex genetic disease, microRNAs discovery, miRNAs in physiological processes, Alterations of non-coding RNAs in human disease, ncRNA expression profiles in cancer, Abnormal miRNA expression – “in cascade” model, A non-coding RNA revolution in the cancer society, microRNAs as oncogenes and tumor suppressors, miR alterations and cancer predisposition, SNPs in miRs could predispose to familial cancer, microRNAs in plasma, miRNAs as new therapeutic targets & drugs, lncRNAs – mechanisms of action